Is Mycoplasma genitalium in women the "New Chlamydia?" A community-based prospective cohort study. - Oakeshott, P; Aghaizu, A; Hay, P; Reid, F; Kerry, S; Atherton, H; Simms, I; Taylor-Robinson, D; Dohn, B; Jensen, J (2010)
BACKGROUND: The role of Mycoplasma genitalium in pelvic inflammatory disease is unclear. We conducted a cohort study to determine the prevalence and predictors of M. genitalium infection in female students, to explore its role in pelvic inflammatory disease and to estimate its annual incidence and persistence rate. METHODS: Two thousand three hundred seventy-eight multiethnic, sexually active female students (mean age, 21 years) provided duplicate self-taken vaginal samples for a chlamydia screening trial. From this population, 2246 (94%) were followed up after 12 months and assessed for incidence of clinical pelvic inflammatory disease. In addition, 900 women (38%) returned follow-up samples via the postal service 11-32 months after recruitment. Stored samples were tested for M. genitalium. RESULTS: The prevalence of M. genitalium at baseline was 3.3% (78 of 2378 women; 95% confidence interval [CI], 2.6%-4.1%). Infection was more common in women reporting ≥ 2 sexual partners in the previous year, those with bacterial vaginosis, women aged < 18 years, women of black ethnicity, and smokers. Multiple partners and bacterial vaginosis were independent risk factors for M. genitalium (adjusted risk ratio, 2.23 [95% CI, 1.39-3.58] and 2.54 [95% CI, 1.61-4.01], respectively). The incidence of pelvic inflammatory disease over 12 months was 3.9% (3 of 77 women) among women with M. genitalium infection, compared with 1.7% (36 of 2169 women) among those without infection (risk ratio, 2.35; 95% CI, 0.74-7.46; P = .14). Annual incidence of M. genitalium infection in 873 women without M. genitalium infection at baseline who returned samples via the postal service was 0.9% (95% CI, 0.5%-1.6%). Seven (26%; 95% CI, 9%-43%) of 27 women with M. genitalium infection at baseline remained positive after 12-21 months; genotyping results suggest that these were persistent infections. CONCLUSIONS: M. genitalium infection is unlikely to be a major risk factor for clinical pelvic inflammatory disease in this population.